Characterization of Ugandan Endemic Aspergillus Species and Identification of Non-Aflatoxigenic Isolates for Potential Biocontrol of Aflatoxins - Wokorach, Godfrey; Landschoot, Sofie; Lakot, Amerida; Arihona Karyeija, Sidney; Audenaert, Kris; Echodu, Richard; Haesaert, Geert (Toxins, 2022)
Acute stunting in children, liver cancer, and death often occur due to human exposure to aflatoxins in food. The severity of aflatoxin contamination depends on the type of Aspergillus fungus infecting the crops. In this study, Aspergillus species were isolated from households’ staple foods and were characterized for different aflatoxin chemotypes. The non-aflatoxigenic chemotypes were evaluated for their ability to reduce aflatoxin levels produced by aflatoxigenic A. flavus strains on maize grains. Aspergillus flavus (63%), A. tamarii (14%), and A. niger (23%) were the main species present. The A. flavus species included isolates that predominantly produced aflatoxins B1 and B2, with most isolates producing a high amount (>20 ug/ L) of aflatoxin B1 (AFB1), and a marginal proportion of them also producing G aflatoxins with a higher level of aflatoxin G1 (AFG1) than AFB1. Some non-aflatoxigenic A. tamarii demonstrated a strong ability to reduce the level of AFB1 by more than 95% when co-inoculated with aflatoxigenic A. flavus. Therefore, field evaluation of both non-aflatoxigenic A. flavus and A. tamarii would be an important step toward developing biocontrol agents for mitigating field contamination of crops with aflatoxins in Uganda.
Keywords: Aspergillus flavus; Aspergillus niger; Aspergillus tamarii; Aflatoxin B1